Highly exposed segment of the Spf1p P5AATPase near transmembrane M5 detected by limited proteolysis - Petrovich, Guido Daniel (2021)
The yeast Spf1p protein is a primary transporter that belongs to group 5 of the large family of P-ATPases. Loss of Spf1p function produces ER stress with alterations of metal ion and sterol homeostasis and protein folding, glycosylation and membrane insertion. The amino acid sequence of Spf1p shows the characteristic P-ATPase domains A, N, and P and the transmembrane segments M1-M10. In addition, Spf1p exhibits unique structures at its N-terminus (N-T region), including two putative additional transmembrane domains, and a large insertion connecting the P domain with transmembrane segment M5 (D region). Here we used limited proteolysis to examine the structure of Spf1p. A short exposure of Spf1p to trypsin or proteinase K resulted in the cleavage at the N and C terminal regions of the protein and abrogated the formation of the catalytic phosphoenzyme and the ATPase activity. In contrast, limited proteolysis of Spf1p with chymotrypsin generated a large N-terminal fragment containing most of the M4-M5 cytosolic loop, and a minor fragment containing the C-terminal region. If lipids were present during chymotryptic proteolysis, phosphoenzyme formation and ATPase activity were preserved. ATP slowed Spf1p proteolysis without detectable changes of the generated fragments. The analysis of the proteolytic peptides by mass spectrometry and Edman degradation indicated that the preferential chymotryptic site was localized near the cytosolic end of M5. The susceptibility to proteolysis suggests an unexpected exposure of this region of Spf1p that may be an intrinsic feature of P5A-ATPases.